Challenges of Adopting Technological Innovations in Start-Up SMEs in Sleman - Sukarno, Agus; Istanto, Yuni; Nusanto, Gunawan; Setiadi, Iwan Kresna; Wardani, Nuruni Ika Kusuma (RSF Conference Series: Business, Management and Social Sciences, 2021)
The Covid-19 pandemic has destroyed many SMEs throughout Indonesia, even in Sleman. This study aims to test the product innovation model on start-up SMEs in Sleman in overcoming the challenges of digital transformation. The technology analyzed in this study is digital technology in start-up SMEs for product marketing and creating new innovative products. The population in this study were all start-up SMEs in Sleman. Sampling using purposive sampling. The number of samples in this study was 75 respondents. This study uses a respondent survey approach. The data analysis technique used qualitative and quantitative analysis. Qualitative analysis was conducted to create a cluster map of the distribution of start-ups and technology clusters used by start-ups in Sleman. Quantitative analysis is used to test the product innovation model at start-ups in Sleman.